Social drivers of maturation age in female geladas. (13th April 2022) - Feder, Jacob A; Beehner, Jacinta C; Baniel, Alice; Bergman, Thore J; Snyder-Mackler, Noah; Lu, Amy
Abstract: Female reproductive maturation is a critical life-history milestone, initiating an individual's reproductive career. Studies in social mammals have often focused on how variables related to nutrition influence maturation age in females. However, parallel investigations have identified conspicuous male-mediated effects in which female maturation is sensitive to the presence and relatedness of males. Here, we evaluated whether the more "classic" socioecological variables (i.e., maternal rank, group size) predict maturation age in wild geladas—a primate species with known male-mediated effects on maturation and a grassy diet that is not expected to generate intense female competition. Females delayed maturation in the presence of their fathers and quickly matured when unrelated, dominant males arrived. Controlling for these male effects, however, higher-ranking daughters matured at earlier ages than lower-ranking daughters, suggesting an effect of within-group contest competition. However, contrary to predictions related to within-group scramble competition, females matured earliest in larger groups. We attribute this result to either: 1) a shift to "faster" development in response to the high infant mortality risk posed by larger groups; or 2) accelerated maturation triggered by brief, unobserved male visits. While earlier ages at maturation were indeed associated with earlier ages at first birth, these benefits were occasionally offset by male takeovers, which can delay successful reproduction via spontaneous abortion. In sum, rank-related effects on reproduction can still occur even when socioecological theory would predict otherwise, and males (and the risks they pose) may prompt female maturation even outside of successful takeovers. Abstract : In social animals, reproductive maturation can be accelerated by nutritional advantages or the arrival of suitable mates. In geladas, the immigration of unrelated males prompts female maturation. Here, we report that—above and beyond this male effect—female geladas mature earlier if their mothers are high-ranking, which likely improves access to high-quality foods, and if they live in large groups, which experience higher rates of infant mortality and more frequent exposure to loitering, unrelated males.